Fulminant bilateral acute retinal necrosis complicated with secondary herpes simplex type-1 viral encephalitis: A case report. Issue 35 (August 2019) - Ye, Lingqi; Ding, Xiansan; Shen, Shanshan; Wang, Jing; Wu, Jimin; Chen, Yanxing
Abstract: Rationale: Acute retinal necrosis (ARN), which is characterized by peripheral necrotizing retinitis, severe retinal arteritis, and progressive inflammatory reaction in the vitreous and anterior chambers, has been reported in cases with herpes simplex encephalitis (HSE). It is a relatively rare complication secondary to HSE. However, cases presented with viral encephalitis following ARN were seldom reported. Patient concerns: A 43-year-old immunocompetent male patient manifested the aforesaid reverse situation. He developed HSE following 3-day systemic steroid therapy for abrupt ocular pain and rapidly decreased visual acuity, which was later diagnosed as ARN. Polymerase chain reaction (PCR) analysis of vitreous specimen verified herpes simplex virus-1 (HSV-1) infection. Diagnosis: HSE associated with ARN. Interventions: The patient was treated with intravenous acyclovir (500 mg every 8 h) for 21 days. A pulse of intravenous methylprednisolone, 500 mg/d for 5 days was given as an anti-inflammatory therapy, followed by prednisone taper. Outcomes: The patient's neurological symptoms got improved very soon after the therapy, but his vision acuity remained no perception of light in both eyes. Lessons: The present case indicates that ARN can also be a risk factor for HSE. Once ARN was suspected, corticosteroid should be applied with caution and in combination with antiviral treatment to avoid progressive duplication of virus and its spread to the brain.